65 The Role of Livestock as up-Cyclers of Food by-Products and Waste. (21st September 2022) - Ominski, Kim; McAllister, Tim A; Stanford, Kim; Mengistu, Genet; Gunte, Kebebe E; Marcos, Marcos; Wittenberg, Karin; Omonijo, Faith; White, Jaime; Legesse, Getahun
Abstract: Food waste is a global dilemma with environmental, social and economic consequences. Environmental impacts of wasted food are substantial as it comprises the single largest category of organic matter in municipal landfills. Therefore, redirection of food waste from landfills is necessary to improve global food security and environmental sustainability issues. Livestock, with their capacity to "up-cycle" relatively low-quality feedstuffs into high quality protein, are an essential element of this solution. However, challenges regarding utilization of food waste for livestock production include regulatory restrictions, safety concerns and logistics associated with collection, transport and handling. Moreover, identifying industries with significant loss and waste resources along the supply chain, quantifying availability, and effective communication and coordination are necessary steps for large-scale diversion of food loss and waste to livestock feed. In Canada, Loop Resources is a one-of-a-kind organization that enables food wholesalers, retailers, and producers to divert unsaleable food away from landfill to local food banks and livestock farmers. They are working with retailers to divert 2.5 – 3.5 million kg of food waste/month to over 2500 farms across Canada. However, today's diversity of by-products and urban setting for much of our food waste requires a diversity of solutions. Producer and processor incentives to recover more food will require investment to improve infrastructure and create market opportunities. Research to facilitate safe incorporation of food waste in animal feed is also a critical step toward changes in policy and regulation. In addition, comprehensive LCA-type assessments will shed light on the environmental benefits of replacing feed grains or forages with by-products or food waste. Finally, a coordinated approach requiring input from producers, food processors, feed suppliers, researchers, policy makers and retailers, is critical for the development of successful strategies for inclusion of food loss and waste in livestock diets.